2000
DOI: 10.1177/096368970000900211
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal Ventral Mesencephalic Xenografts of Porcine Tissue in Rats: Immune Responses and Functional Effects

Abstract: Transplantation of neural tissue from other species has the potential to improve function in patients with neurodegenerative disorders. We investigated the functional effects of embryonic porcine dopaminergic neurons transplanted in a rat model of Parkinson's disease and the immune responses to the grafts in immunosuppressed and nonimmunosuppressed hosts. Twenty-three rats with unilateral 6-hydroxydopamine lesions received dissociated, 27-day-old embryonic porcine ventral mesencephalic tissue in the right stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 51 publications
1
28
1
Order By: Relevance
“…We have shown in previous studies that the porcine neural grafts mature over time, with increased TH expression and outgrowth of axons. We have demonstrated that the porcine grafts are able to restore function in the rat model of Parkinson's disease, after a maturation process that takes between 6 and 9 wk [15]. In that study, we immunosuppressed the rats with a high dose of cyclosporine A, and around 50% of the grafts were rejected at 14 wk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown in previous studies that the porcine neural grafts mature over time, with increased TH expression and outgrowth of axons. We have demonstrated that the porcine grafts are able to restore function in the rat model of Parkinson's disease, after a maturation process that takes between 6 and 9 wk [15]. In that study, we immunosuppressed the rats with a high dose of cyclosporine A, and around 50% of the grafts were rejected at 14 wk.…”
Section: Discussionmentioning
confidence: 99%
“…The graft volumes and the number of TH-positive cells were obtained using a stereological analysis system described earlier [15]. A CAST-Grid software package (Interactivision, Silkeborg, Denmark) was used to obtain cell counts by randomly and systematically placing a counting frame over the delineated transplant.…”
Section: Stereological and Statistical Methodsmentioning
confidence: 99%
“…This suggests that such an approach might be useful clinically to improve graft survival, possibly by removing the more immunogenic cells. Conventional immunosuppressive drugs used as monotherapy (e.g., cyclosporin A or tacrolimus) do not protect grafts effectively, [65][66][67] but this can be improved if combined with other drugs such as prednisolone. 65 Short courses of treatment with molecules that block T-cell costimulation [CD40L, LFA1, and CTLA4Ig (40,41)] have resulted in very good graft survival in mice, although long-term studies are needed to determine whether this therapy could be used clinically.…”
Section: Xenogeneic Neural Graftsmentioning
confidence: 99%
“…Since cyclosporine treatment acts primarily to inhibit T lymphocyte-mediated immunity [251,252], these findings indicate the involvement of other arms of the immune system, such as innate immunity, in MSC graft rejection. In addition, cyclosporine treatment for neural xenotransplantation has been reported to be suboptimal [253,254]. Furthermore, complement factors, immunoglobulins and macrophages may be involved in immune responses against discordant xenografts, and these are not affected in a crucial way by cyclosporine treatment [255][256][257].…”
Section: Activation Of Innate Immune Response With Intracerebral Msc mentioning
confidence: 99%